Systematic review of effects of current transtibial prosthetic socket designs—Part 1: Qualitative outcomes - Safari, Mohammad Reza; Meier, Margrit Regula (Journal of rehabilitation research and development, 2015)
This review is an attempt to untangle the complexity of transtibial prosthetic socket fit, determine the most important characteristic for a successful fitting, and perhaps find some indication of whether a particular prosthetic socket type might be best for a given situation. Further, it is intended to provide directions for future research. We followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and used medical subject headings and standard key words to search for articles in relevant databases. No restrictions were made on study design or type of outcome measure. From the obtained search results (n = 1,863), 35 articles were included. The relevant data were entered into a predefined data form that incorporated the Downs and Black risk of bias assessment checklist. Results for the qualitative outcomes (n = 19 articles) are synthesized. Total surface bearing sockets lead to greater activity levels and satisfaction in active persons with amputation, those with a traumatic cause of amputation, and younger persons with amputation than patellar tendon bearing sockets. Evidence on vacuum-assisted suction and hydrostatic sockets is inadequate, and further studies are much needed. To improve the scientific basis for prescription, comparison of and correlation between mechanical properties of interface material, socket designs, user characteristics, and outcome measures should be conducted and reported in future studies.